Primary spindle‐cell sarcomas of the breast: Diagnosis by fine‐needle aspiration - Stanley, Michael W. [UNESP] (1988)
Primary breast sarcomas (excluding cystosarcoma phyllodes and its sarcomatous recurrences) are rare neoplasms. Few have been described in the aspiration cytology literature. We report the cytologic features of two cases of stromal sarcoma (both with the pattern of malignant fibrous histiocytoma) and two cases of angiosarcoma. The dominant cytologic features included individual atypical spindle cells and fragments of collagenous stroma. Tumor giant cells were present in one stromal sarcoma. Features of possible significance in the diagnosis of angiosarcoma include obvious vessel formation by atypical spindle cells, bridging of adjacent tumor fragments by spindle cells, and microacinar structures lined by atypical spindle cells. The differential diagnostic considerations in spindle‐cell breast aspirations are discussed. Copyright © 1988 Wiley‐Liss, Inc., A Wiley Company